Quadratic frequency comb based on phase-modulated cw-driven optical parametric oscillator with intracavity dispersion control - A. D. Sanchez; S. Chaitanya Kumar; M. Ebrahim-Zadeh (Physical Review Research)
We report a novel configuration of bulk χ^{(2)} optical parametric oscillator (OPO) capable of delivering coherent broadband phase-locked spectrum when driven by a continuous-wave (cw) pump laser. By deploying an electrooptic modulator (EOM) internal to a degenerate cw OPO based on MgO:sPPLT or MgO:PPLN and implementing intracavity dispersion control, we show that output spectra extending over 9 nm (119 nm) with well-defined phase coherence can be generated. Pumping the cw OPO at 532 nm (1550 nm) for degenerate operation in the normal (anomalous) dispersion regime at 1064 nm (3100 nm), and using the coupled-wave equations to simulate the OPO in the presence of intracavity dispersion compensation, we demonstrate that this device offers a new alternative for χ^{(2)}-based frequency comb generation. We also show that in the time domain the output of such a device corresponds to femtosecond quadratic solitons in both dispersion regimes. The described concept is generic, paving the way for the realization of a new class of coherent broadband frequency comb sources in different spectral regions based on χ^{(2)} OPOs pumped by cw lasers.